Extracellular Phosphorylation of TIMP-2 by Secreted c-Src Tyrosine Kinase Controls MMP-2 Activity - Sánchez-Pozo, Javier (iScience, 2018)
The tissue inhibitor of metalloproteinases 2 (TIMP-2) is a specific endogenous inhibitor of matrix metalloproteinase 2 (MMP-2), which is a key enzyme that degrades the extracellular matrix and promotes tumor cell invasion. Although the TIMP-2:MMP-2 complex controls proteolysis, the signaling mechanism by which the two proteins associate in the extracellular space remains unidentified. Here we report that TIMP-2 is phosphorylated outside the cell by secreted c-Src tyrosine kinase. As a consequence, phosphorylation at Y90 significantly enhances TIMP-2 potency as an MMP-2 inhibitor and weakens the catalytic action of the active enzyme. TIMP-2 phosphorylation also appears to be essential for its interaction with the latent enzyme proMMP-2 in vivo. Absence of the kinase or non-phosphorylatable Y90 abolishes TIMP-2 binding to the latent enzyme, ultimately hampering proMMP-2 activation. Together, TIMP-2 phosphorylation by secreted c-Src represents a critical extracellular regulatory mechanism that controls the proteolytic function of MMP-2.